Perfil e padr\~oes de acesso repetido ao seguro-desemprego no Brasil - Brunu Amorim; Victória Evellyn Costa Moraes Sousa; Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study analyzes the implementation of unemployment insurance in Brazil, with an emphasis on the patterns of repeated access to the benefit by workers with formal employment relationships. We consider two subperiods - 2007-2012 and 2014-2019 - which, in addition to being different in the recent history of the Brazilian economy, are permeated by an institutional change that altered the rules for access to the benefit (Law No. 13,134/2015). The access patterns were tabulated based on sociodemographic and labor aspects of the beneficiaries. The repeated access patterns of beneficiaries who return to the same employer are also investigated. Regarding the results, two points can be highlighted: i) the repeated access rates to unemployment insurance found for Brazil were not high compared to the international literature, demonstrating that this does not seem to be a problem that significantly compromises the structure and sustainability of the program in the country; and ii) the workers who used unemployment insurance the most were those groups whose characteristics indicate a greater likelihood of being subject to unstable employment relationships. It is expected that this analytical exercise can provide support for the discussion on the design of the program, in conjunction with the Brazilian Public Employment, Labor and Income System (SPETR).
Keywords: J06; J65; J68; 330; unemployment insurance; repeated access; labor market; social protection; public policies